Stable control of networked robot subject to communication delay, packet loss, and out-of-order delivery - Phung, Manh Duong; Tran, Thuan Hoang; Tran, Quang Vinh (Vietnam Journal of Mechanics, 2014)
Stabilization control of networked robot system faces uncertain factors caused by the network. Our approach for this problem consists of two steps. First, the Lyapunov stability theory is employed to derive control laws that stabilize the non-networked robot system. Those control laws are then extended to the networked robot system by implementing a predictive filter between the sensor and controller. The filter compensates influences of the network to acquire accurate estimate of the system state and consequently ensures the convergence of the control laws. The optimality of the filter in term of minimizing the mean square error is theoretically proven. Many simulations and experiments have been conducted. The result confirmed the validity of the proposed approach.